Scientific experiment focused at pigment degradation by polyvinyl chloride combustion in Science education - Zita Jenisová; Jana Braniša (OmniaScience, 2019)
The Environmental education navigates students towards environmentally friendly life style and securing a quality of life. The implementation of cross-section topics, including the Environmental education, into science classes, is possible through a variety of techniques. One of the least used methods is a real school experiment. The following paper presents the experiment, by which we simulate the combustion of PVC and observe the impact of combustion products on plants via UV-Vis spectrophotometry optical method. This method is suitable for qualification and analysis of vegetable pigments, i.e. chlorophylls, carotenoids, and anthocyanins. The experiment is integrated into the Techniques and Didactics of School Chemistry Experiments as a part of master degree course, which prepares students for the Chemistry teaching profession. The introduced experiment enables pedagogues to integrate the environmental education into teaching process and develop mathematical and science literacy of students in the Chemistry education.